Conflict Resolution and Peacemaking in Islam: Toward Reconciliation and Complementarity between Western and Muslim Approaches - Rehman, Uzma (Islamic Studies, 2011)
The current debate at the popular as well as academic levels about religions’ role in the present conflicts requires further research. The question whether or not religion is the main factor behind the current conflicts is being dealt with by a number of academics and researchers. This paper goes a step further into the study of religions’ role in conflict resolution. The potential role of religions in conflict resolution and peacemaking has become a necessary phenomenon since religious ideologies have been hijacked by their very adherents in order to legitimize actions driven either by political ends and power interests or due to a general sense of frustration and desperation produced by injustice towards and marginalization of certain groups who happen to be adherents of a certain religious tradition. The arguments for the importance of the role of religion in conflict resolution point to the enormous mobilizing power of religions, code of ethics, high human principles, cultural norms and values highlighted by religious traditions and their specific teachings and concepts about conflict and reconciliation; war and peace, etc. This paper focuses on conflict resolution and peacemaking in Islam, a religion which, in current circumstances as well as historically, has mostly been associated with conflict and war. This study of conflict resolution which does not entirely respond to specific situations in a nonWestern Muslim cultural context. The paper briefly mentions the indigenous Arab/Islamic tradition of conflict resolution while discussing Islamic conflict resolution models which draw on the original Islamic sources and teachings as well as creating a common ground where the Western principles of conflict resolution can be accommodated. A study of Islamic concepts of peace and conflict/war could contribute to the discussion related to conflict resolution and peacemaking in Islam.